Wheel tracking rutting performance estimation based on bitumen Low Shear Viscosity (LSV), loading and temperature conditions - Morea, Francisco (2014)
The development of new technologies and road pavement materials require the evaluation of the asphalt mixture performance. Rutting is one of the main modes of failure of asphalt mixtures; it is typically studied at the laboratory through the wheel tracking test (WTT). Weather and traffic conditions (temperature, loads) significantly affect the pavement rutting performance. The bitumen rheological properties also have a main role in mixture rutting response; they can adequately characterized by the bitumen Low Shear Viscosity (LSV). The estimation of rutting performance appears as a useful decision tool to optimize pavement design process. This paper studies the rutting performance of asphalts mixtures utilising the WTT. The specimens were tested at different temperatures and loading levels to simulate different climatic and traffic pavement conditions. A performance estimator was developed including temperature and traffic load on the pavement, and LSV of the binder as input data.